Resin-Bonded Fiber-Reinforced Composite for Direct Replacement of Missing Anterior Teeth: A Clinical Report - Sufyan Garoushi; Lippo Lassila; Pekka K. Vallittu (Hindawi Limited, 2011)
Missing anterior teeth is of serious concern in the social life of a patient in most of societies. While conventional fixed partial dentures and implant-supported restorations may often be the treatment of choice, fiber-reinforced composite (FRC) resins offer a conservative, fast, and cost-effective alternative for single and multiple teeth replacement. This paper presents two cases where FRC technology was successfully used to restore anterior edentulous areas in terms of esthetic values and functionality.